Evaluation of nitrous acid sources and sinks in urban outflow. (February 2016) - Gall, Elliott T.; Griffin, Robert J.; Steiner, Allison L.; Dibb, Jack; Scheuer, Eric; Gong, Longwen; Rutter, Andrew P.; Cevik, Basak K.; Kim, Saewung; Lefer, Barry; Flynn, James
Abstract: Intensive air quality measurements made from June 22–25, 2011 in the outflow of the Dallas–Fort Worth (DFW) metropolitan area are used to evaluate nitrous acid (HONO) sources and sinks. A two-layer box model was developed to assess the ability of established and recently identified HONO sources and sinks to reproduce observations of HONO mixing ratios. A baseline model scenario includes sources and sinks established in the literature and is compared to scenarios including three recently identified sources: volatile organic compound-mediated conversion of nitric acid to HONO (S1), biotic emission from the ground (S2), and re-emission from a surface nitrite reservoir (S3). For all mechanisms, ranges of parametric values span lower- and upper-limit values. Model outcomes for 'likely' estimates of sources and sinks generally show under-prediction of HONO observations, implying the need to evaluate additional sources and variability in estimates of parameterizations, particularly during daylight hours. Monte Carlo simulation is applied to model scenarios constructed with sources S1–S3 added independently and in combination, generally showing improved model outcomes. Adding sources S2 and S3 (scenario S2/S3) appears to best replicate observed HONO, as determined by the model coefficient of determination and residual sum of squared errors ( r 2 = 0.55 ± 0.03, SSE = 4.6 × 10 6 ± 7.6 × 10 5 ppt 2 ). In scenario S2/S3, source S2 is shown to account for 25% and 6.7% of the nighttime and daytime budget, respectively, while source S3 accounts for 19% and 11% of the nighttime and daytime budget, respectively. However, despite improved model fit, there remains significant underestimation of daytime HONO; on average, a 0.15 ppt/s unknown daytime HONO source, or 67% of the total daytime source, is needed to bring scenario S2/S3 into agreement with observation. Estimates of 'best fit' parameterizations across lower to upper-limit values results in a moderate reduction of the unknown daytime source, from 0.15 to 0.10 ppt/s. Highlights: A two-layer box model evaluates HONO sources, sinks in outflow of Dallas–Fort Worth. Monte Carlo simulation is applied to scenarios with 3 recently identified sources. Improved model outcomes result from inclusion of 2 of 3 recently identified sources. A substantial unknown source is still required for agreement with observation. Missing HONO source is moderately correlated with jNO2, weakly correlated with NO2 .